1986
DOI: 10.1007/bf03014260
|View full text |Cite
|
Sign up to set email alerts
|

Esmolol for control of increases in heart rate and blood pressure during tracheal intubation after thiopentone and succinylcholine

Abstract: Esmolol, an ultra-short-acting cardioselective betaadrenergic blocker, was investigated in a double-blind prospective protocol for its ability to control haemodynamic responses associated with tracheal intubationEsmolol is a cardioselective, beta-adrenergic blocking agent with a short duration of action because it is metabolized by a blood esterase,l The short duration of action permits rapid titration by intravenous infusion to a desired level of beta blockade. Likewise, cessation of esmolol infusion rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 34 publications
3
26
0
2
Order By: Relevance
“…23,26,29,30,33,35,38,39,48 Heart rate achieved was not significant for any of the efficacy outcomes apart from non-fatal myocardial infarction-trials that achieved heart rate of 75 beats per min or less reported a lower reduction in risk than did the other group (tables 2 and 3).…”
Section: Weight (%)mentioning
confidence: 96%
See 3 more Smart Citations
“…23,26,29,30,33,35,38,39,48 Heart rate achieved was not significant for any of the efficacy outcomes apart from non-fatal myocardial infarction-trials that achieved heart rate of 75 beats per min or less reported a lower reduction in risk than did the other group (tables 2 and 3).…”
Section: Weight (%)mentioning
confidence: 96%
“…High-bias risk trials Coleman 42 Lai 35 Liu 36 Magnusson 36 POBBLE 3 Poldermans 32 Stone 38 Urban 39 Zaugg 33 Liu 48 33 trials included 12 306 patients having non-cardiac surgery, 6311 (51%) patients randomly assigned to the β-blocker group, and 5995 (49%) to the control group. The β blocker used, dose given, timing of administration, and the duration of administration varied in the trials (table 1).…”
Section: Myocardial Ischaemiamentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded nine studies which reported only major cardiovascular complications within 30 days of surgery [1,2,[21][22][23][24][25][26][27] and a further nine studies which did not present data on perioperative myocardial ischaemia [28][29][30][31][32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%